PEMANFAATAN KULIT JERUK (CITRUS SINENSIS) SEBAGAI PEKTIN BAGI PENDERITA KOLESTROL TINGGI (HIPERKOLESTROL):TINJAUAN LITERATUR - Anastasia Nandya Septianingrum; Nashuha Faza Wuryaningtyas; Fadli Ash-Shiddiqi; Rahma Risky Nabila Putri; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2023)
High cholesterol levels or commonly known as hypercholesterolemia in the blood is one of the triggers for hypertension. This happens with the presence of high cholesterol which is the cause of blockages in the peripheral blood vessels which will reduce the blood supply to a person's heart. Hypercholesterolemia itself is a condition in which the concentration of cholesterol in the blood increases which exceeds or exceeds the normal value that should be. it turns out that orange peel in small quantities contains 30% pectin on a dry basis, pectin itself is a natural substance found in parts of food plants. The purpose of this study was to determine the use of orange peel as pectin in people with high cholesterol. The method in this research is to use a type of qualitative research method. The research design used was a literature review design. The results of this study indicate that the pectin producer comes from orange peels, pectin itself is a natural ingredient found in most food plants, besides that it is also a structural element in the growth of tissues and the main component of the middle lamella. plant. In addition, pectin functions as an adhesive and maintains the stability of tissues and cells. This pectin is used as a thickener in jelly making and also in low-calorie foods. By consuming pectin can reduce the risk of high cholesterol disease. Keywords: orange peel, pectin, cholesterol sufferers